Inside Cover Image, Volume 8, Issue 1 - Shimokawa, Tomoko (Food Sci Nutr, 2020)
The cover image is based on the ORIGINAL RESEARCH Component features, odor‐active volatiles, and acute oral toxicity of novel white‐colored truffle Tuber japonicum native to Japan by Tomoko Shimokawa et al., https://doi.org/10.1002/fsn3.1325. Cover Credit: Cover image ©Tomoko Shimokawa Images [Image: see text]